Therapeutic Outcomes of Haploidentical Allogeneic Hematopoietic Stem Cell Transplantation in Patients With Severe Aplastic Anemia: A Multicenter Study. Issue 10 (October 2018) - Li, Yonghua; Duan, Fengqi; Xiao, Haowen; Wu, Xiaoxiong; Wang, Shunqing; Xu, Duorong; Liu, Qifa; Fan, Zhiping; Nie, Danian; Lai, Yongrong; Wu, Bingyi; Lin, Dongjun; et al.
Abstract : Background: Haploidentical donor (HID) allogeneic hematopoietic stem cell transplantation (HSCT) is an alternative curative treatment for patients with severe aplastic anemia (SAA) who do not have suitable matched related donors (MRD). The aim of this study was to compare the therapeutic outcomes of HID-HSCT with those of MRD-HSCT for SAA. Methods: A total of 235 SAA patients who underwent HID-HSCT (116) or MRD-HSCT (119) at 11 transplantation centers from January 2007 to January 2016 were included. Complications and survival outcomes were evaluated and compared between the 2 groups. Results: The HID group had a lower incidence of secondary graft failure but higher incidences of acute graft-versus-host disease (aGVHD) and chronic GVHD (cGVHD). However, the incidence of severe aGVHD (grades III-IV), poor graft function, and infections was comparable between groups. Patients in the HID group had a significantly lower survival and overall survival rates than those in the MRD group. The estimated 3-year survival rates for the MRD and HID groups were 82.82% and 75.00%, respectively. Ferritin levels, graft failure, poor graft function, severe aGVHD, and infections were the significant risk factors for survival. Conclusions: The overall survival rate is acceptable for patients who underwent HID-HSCT, making it a feasible treatment choice for SAA patients. Abstract : In this retrospective multicenter study in patients with severe aplastic anemia, the authors report on acceptable results in patients receiving haploidentical donor allogeneic hematopoietic stem cell transplantation when compared to those receiving a matched-related donor.